2014
DOI: 10.1021/bi500664w
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsically Disordered C-RING Biomineralization Protein, AP7, Creates Protein Phases That Introduce Nanopatterning and Nanoporosities into Mineral Crystals

Abstract: We report an interesting process whereby the formation of nanoparticle assemblies on and nanoporosities within calcite crystals is directed by an intrinsically disordered C-RING mollusk shell nacre protein, AP7. Under mineralization conditions, AP7 forms protein phases that direct the nucleation of ordered calcite nanoparticles via a repetitive protein phase deposition process onto calcite crystals. These organized nanoparticles are separated by gaps or spaces that become incorporated into the forming bulk cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(75 citation statements)
references
References 10 publications
8
67
0
Order By: Relevance
“…Calcium carbonate formation in shells, for example, is regulated by IDPs. One shell protein, AP7, first shown to form supramolecular-assemblies and nucleate single crystals of aragonite [36] is also involved in the regulation of calcite growth [37]. The C-RING-like sequence is an important site for AP7 self-association and mineral nucleation; self-assembling, to form protein phases that congregate amorphous calcium carbonate nanoparticles, into hybrid, protein–mineral supramolecular networks, and create nano-porosities on the surfaces of the calcite that forms.…”
Section: Intrinsically Disordered Proteins (Idps)mentioning
confidence: 99%
See 2 more Smart Citations
“…Calcium carbonate formation in shells, for example, is regulated by IDPs. One shell protein, AP7, first shown to form supramolecular-assemblies and nucleate single crystals of aragonite [36] is also involved in the regulation of calcite growth [37]. The C-RING-like sequence is an important site for AP7 self-association and mineral nucleation; self-assembling, to form protein phases that congregate amorphous calcium carbonate nanoparticles, into hybrid, protein–mineral supramolecular networks, and create nano-porosities on the surfaces of the calcite that forms.…”
Section: Intrinsically Disordered Proteins (Idps)mentioning
confidence: 99%
“…The C-RING-like sequence is an important site for AP7 self-association and mineral nucleation; self-assembling, to form protein phases that congregate amorphous calcium carbonate nanoparticles, into hybrid, protein–mineral supramolecular networks, and create nano-porosities on the surfaces of the calcite that forms. Chang et al [37] speculated that the repeated deposition of AP7 on the calcite surface allows for the creation of these nano-porosities. The ability of IDPs to interact with and regulate more than one mineral phase is another important theme that will occur throughout this discussion.…”
Section: Intrinsically Disordered Proteins (Idps)mentioning
confidence: 99%
See 1 more Smart Citation
“…12-19 These families include the framework, intracrystalline, and pearl/reparative proteomes 12-26 that are localized throughout the nacre layer. Recent experiments have shown that 4 representative nacre proteins (AP7, 13-15 PFMG1, 18 n16.3, 16,17 Pif97 12 ) exist as intrinsically disordered, aggregation-prone species that spontaneously form hydrogels or protein phases under both low and high ionic strength conditions. 12-17 These phases have been shown to organize and assemble amorphous calcium carbonate (ACC) nanoparticles during the early stages of calcium carbonate nucleation and control the formation kinetics of pre-nucleation clusters (PNCs), the predecessors of ACC.…”
mentioning
confidence: 99%
“…For this, we created a model combinatorial system consisting of two intrinsically disordered nacre proteins, the intracrystalline shell nacre protein, AP7 ( Haliotis rufescens , 66 AA, C-RING domain 31-66, chemically synthesized form = cAP7) 13-15 and the pearl-associated nacre protein, PFMG1 ( Pinctada fucata , 116 AA, pseudo-EF hand domain 61-110, bacterial recombinant form = rPFMG1)(Figure S1, Supporting Information). 18,21 The C-RING-containing cAP7 forms hydrogels that induces the formation of intracrystalline nanoporosities and nanotexturing or nanopatterning on the exposed surfaces of calcite.…”
mentioning
confidence: 99%